Advanced control design for HDD in mobile consumer devices - Wang, Jianyi (2011)
As the HDD finds more applications in various mobile consumer devices, HDD servo control needs to improve the performance in the seeking acoustics and vibration rejection. This research provides feasible solutions to these two problems. The work described in this thesis is summarized as follows: